Dual energy CT in radiotherapy: Current applications and future outlook. Issue 1 (April 2016) - van Elmpt, Wouter; Landry, Guillaume; Das, Marco; Verhaegen, Frank
Abstract: Dual energy CT (DECT) scanners are nowadays available in many radiology departments. For radiotherapy purposes, new strategies using DECT imaging are investigated to optimize radiation treatment for multiple steps in the radiotherapy chain. This review describes how DECT based methods can be used for electron density estimation, effective atomic number decomposition and contrast material quantification. Clinical radiotherapy related applications for improved dose calculation accuracy of brachytherapy and proton therapy, metal artifact reduction techniques and normal tissue characterization are also summarized together with future perspectives on the use of DECT for radiotherapy purposes.